Blood biochemical profile in relation to age and reproductive status of Holstein Friesian cattle reared under tropical climate - DHAMI, A J; LAKUM, P D; PATEL, P M; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2005)
This study was planned to evaluate haemoglobin content and certain blood biochemical constituents of HF cattle reared under tropical climate in relation to different age groups and physiological status. All 72 female animals ( 6 in each group) were selected at random from the HF herd according to their age and physiological status, viz., 1-2 weeks, 2-3 months, 5-6 months, 8-9 months, 11- 12 months and 17-18 months old and of varied reproductive status, viz., cyclic/early pregnant heifers (22-24 months old), advanced pregnant heifers (30-36 months old), recently calved cows (0 day), cyclic/lactating cows (2 months postpartum), anoestrus cows (5- 6 months post-partum) and repeat breeder cows (6-9 months postpartum). Hepariniz.ed venous blood samples were obtained once from all animals at specified age/status for this study. The mean Hb content of blood varied from 9.00±0.43 to 11.03±0.22 g% (P-dl.01) with a pooled mean of 9.91::t:0.16 g%. Similarly, the mean values of different biochemical constituents, viz., plasma total protein, triglycerides, calcium phosphorus and Ca:P ratio varied between different groups from 6.02±0.35 to 9.63±0.78 g% (P-dl.05), 9.56±2.16 to 28.94±4.05 mg% (P<0.01), 9.92±0.59 to 12.16±0.73 mg% 8.57::t:0.31 to 12.15::t:0.47 mg% (P-dl.01) and 0.95::t:0.03 to 1.42::t:0.18 (P<0.05), with an overall mean of 7.25±0.19 g%, 19.17±1.15 mg%, 11.53::t:0.17 mg%, 10.19±0.24 mg% and 1.18::t:0.04, respectively. Hb content was lowest in young calves and increased with advancing age to reach highest level at puberty. Total protein content, which was lowest in 1-2 weeks old calves, increased gradually with advancing age till maturity/calving and lactation, but was significantly low in anoestrus and repeat breeding cows. Triglycerides dropped drastically from highest level at birth to lowest level by 3 months of age and thereafter fluctuated in narrow range only, and it was lowest in lactating, anoestrus and repeat breeding cows. Both calcium and phosphorus levels were found lowest in recently calved cows compared to other age groups or reproductive status. The Ca:P ratio, which was wider (1.4:1) in the early age, reduced with advancing age till maturity to almost 1:1, again rose in pregnant and parturient animals, and dropped in anoestrus/repeat breeders cows.